IDENTIFIKASI GAYA ARSITEKTUR BIZANTIUM PADA MASJID 99 KUBAH DI KOTA MAKASAR - Afin Ulul Azmi; Muhil Frido Heriyanto; Ainur Rokhmah (DEARSIP : Journal of Architecture and Civil, 2024)
Architecture is a reflection of a society's culture and history. Mosques, as centers of worship for Muslims, not only serve as places of worship but also reflect cultural and historical richness. The 99 Dome Mosque in Makassar is an example that showcases the influence of Byzantine architecture in its design. This study aims to investigate the influence of Byzantine architecture on the design of the 99 Dome Mosque using qualitative research methods and descriptive analysis. The research identifies Byzantine architectural elements present in the mosque's design and analyzes the architectural characteristics and design elements that reflect this influence. The results show that the 99 Dome Mosque has significant Byzantine architectural influences, evident in its use of large domes and rich ornaments. This study also explores the connection between the mosque's design and historical architectural traditions during the Roman, Persian, and Turkish eras. The conclusion of this study indicates that mosque architecture in Indonesia can serve as an effective medium to reflect and honor cultural heritage and enrich the diversity of local and regional architecture